Management of brinjal shoot and fruit borer leucinodes orbonalis guenee using different approaches (Bangladesh Journal of Agricultural Research, 2017)
The present study was conducted during October 2014 to June 2015 in the farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur to find out the most effective management option (s) against brinjal shoot and fruit borer (BSFB) with 6 treatments namely, Beauveria bassiana, 1´109 CFU @ g l-1, Bioneem 0.3 EC (Azadirachtin) @ 1.5 ml l-1, Tracer 45 SC (Spinosad) @ 0.4 ml l-1, Vertimec 1.8 EC (Abamectin) @ 1.2 ml l-1 of water, Mechanical control (hand picking) with clean cultivation and untreated control. Results revealed that shoot infestation at pre-fruiting stage was the lowest in Bioneem 0.3 EC (4.34%) and at fruiting stage in Tracer 45 SC treated plot (7.75%) and the highest was in untreated control plot (17.94% at pre-fruiting stage and 39.46 at fruiting stage). The lowest fruit infestation by BSFB was obtained with Tracer 45 SC (8.16% n/n and 10.0% w/w) followed by B. bassiana, 1´109 CFU (23.23% n/n and 18.27% w/w) and the highest infestation was observed under untreated control plot (48.59% n/n and 32.09% w/w). Percent reduction of infested fruit by number (83.21%) and weight (68.84%) over untreated control was higher in Tracer 45 SC treated plot resulting significantly higher marketable yield. Therefore, the significant highest marketable yield (34.39 t ha-1) was harvested in the plot treated with Tracer 45 SC followed by 22.78 t ha-1 with B. bassiana, 1´109 CFU and 19.26 t ha-1 from Vertimec 1.8 EC treated plot. The highest benefit cost ratio of 3.05 was obtained from Tracer 45 SC followed by 2.93 in B. bassiana, 1´109 CFU and 2.89 with Vertimec 1.8 EC sprayed plot.Bangladesh J. Agril. Res. 42(3): 539-548, September 2017